Pengaruh Musik sebagai Media Intervensi Terhadap Kemampuan Anak Berbahasa: Tinjauan Literatur Sistematis - Lanang Riyadi; Yudi Sukmayadi (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2023)
Purpose: The purpose of this article is to provide an overview of the phenomenon of music intervention on children's language skills. Music interventions are commonly used for children with special needs, but there are advantages to using music as a medium of intervention for children in general. Method: Systematic literature review is the method in this research with the SPIDER strategy. Result and Discussion: The results found eight selected studies that were relevant to the inclusion criteria. The samples were early childhood and elementary school-aged children whose interest phenomenon included musical activities such as listening and singing songs. The interventions were conducted with various designs and evaluations, and the selected research types covered both quantitative and qualitative approaches. Conclusion: This research implies that the overall research in the intervention can improve children's ability in language. It is expected to be a reference, reference, and comprehensive understanding for educators to conduct music interventions for children's language skills.